2019
DOI: 10.1177/0194599819837244
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Video Head Impulse Test and Caloric Testing among Patients with Vestibular Schwannoma

Abstract: Objective To determine relationships between caloric testing (CT) and video head impulse testing (vHIT) among patients with unilateral vestibular schwannoma (VS). To describe the distribution of CT and vHIT measurements and assess associations with tumor size and self-perceived handicapping effects. Study Design Retrospective review. Setting Tertiary referral hospital. Subjects and Methods Subjects were adults with presumed unilateral VS between 2014 and 2017. Interventions were CT and vHIT. Primary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…The prevalence of abnormal caloric reduction was high across all studies, ranging from 62 to 72%. Two studies (4,5) examined the relationship between vestibular function test results and patient-reported symptoms using the Dizziness Handicap Inventory (DHI) and neither concluded that there was a statistically significant association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of abnormal caloric reduction was high across all studies, ranging from 62 to 72%. Two studies (4,5) examined the relationship between vestibular function test results and patient-reported symptoms using the Dizziness Handicap Inventory (DHI) and neither concluded that there was a statistically significant association.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, impairment of ipsilesional vestibuloocular reflex (VOR) function is well described in VS, with most studies showing a correlation between gain of the VOR and tumor size (2)(3)(4)(5). A small number of case series also report that bilateral VOR impairment may also occur in VS in 6 to 58% of patients but there is a general paucity of literature regarding this phenomenon.…”
mentioning
confidence: 99%
“…In the literature, the sensitivity of vestibular tests in VS patients has mainly been determined with only some of the vestibular tests in each study, diverse methods, diverse definitions of a pathologic result, and different tumor sizes, thus it is difficult to compare the sensitivities of the tests related to each other. The sensitivities are reported to be 62% to 72% for the caloric test, 4,13,14 27% to 90% for lateral canal vHIT, 9,12-15 50% to 73% for oVEMP, 9,16,17 and 50% to 79% for cVEMP. 9,16,18 Lateral and posterior canal vHIT have been found to be more sensitive than anterior canal vHIT, 9,15,19 with sensitivities ranging from 27% to 57% and 8% to 36%, respectively.…”
Section: Comparison With Previous Studies In Vs Patientsmentioning
confidence: 96%
“…Interestingly, Brown et al describe abnormal findings on Cal in 63%, and abnormal gains on the ipsilateral side in 31.4% on vHIT testing for 51 patients with VS. They also report that caloric weakness was associated with tumor size, and that there were no cases with abnormal vHIT and normal Cal [ 72 ]. It appears that Cal is more sensitive to detect vestibular abnormalities in patients with VS.…”
Section: Vestibular Schwannomamentioning
confidence: 99%